Living Quran: Pembiasaan Membaca Asmaul Husna di Sekolah Dasar - Usmi, Fahrul; Kadri, Raja Muhammad (STAI Auliaurrasyidin Tembilahan, 2021)
This paper is a research report on the practice of living Quran in school toward habituating the reading of Asmaul Husna. The purpose of this study was to explore its implementation in the primary school (SD) Sabbihisma 2 Padang. The design was descriptive qualitative research by collecting the data using observation, interviews, and documentation. The findings show that, first, the habit of reading Asmaul Husna has been a long program and characteristic of SD Sabbihisma. Second, in reading Asmaul Husna there was a particular rhythm called the Hijaz rhythm. Third, the reading was accomplished by students every day before the class and during the recitation program at weekly and monthly meetings. Fourth, reading Asmaul Husna was guided by the classroom teacher or teacher who entered in the first hour, it was also led by a teacher/Ustaz. Fifth, the purpose or motivation in reading Asmaul Husna was to expect rewards and heaven from Allah.